A study of risk behavior for orthorexia nervosa among health-related college students: a review of the Brazilian literature (Research, Society and Development, 2022)
Orthorexia nervosa (ON) is a new type of eating behavior abnormality characterized by an exaggerated concern with food quality and dietary purity. This can have consequences in several areas of the lives of affected individuals. Health students are considered the most vulnerable to develop risk behaviors for ON. Thus, through a literature review, the objective is to describe the studies developed in the national territory, on the risk behavior for ON among university students in the health area. The search process was carried out in June and July 2021 in the BIREME, Pubmed, LILACS, SciELO and Google Scholar databases, using the descriptors Orthorexia, Orthorexia nervosa, Orthorexia nervosa “and” nutrition students, Orthorexia nervosa “and” students and their respective terms in english. 252 studies were found on the topic, after applying the exclusion criteria, eight studies were selected. From the data analysis, it was found that students in the health area have a higher prevalence for risk behavior of ON, more in the nutrition course, which may be related to the greater knowledge of healthy eating and its health benefits. Females were the most affected in the studies, but it may also be present among male students. However, all the characteristics of this behavior are not yet well defined, being necessary to carry out further research in the area in order to better elucidate this new change in eating behavior.